The Effect of Topical Extravirgin Olive Oil on Ultraviolet B-Induced 8-Hydroxy-2-Deoxyguanosine Formation in Human Skin - Arief Budiyanto, Irianiwati, Catharina Sagita Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Ultraviolet B (UVBI may cause DNA damage due to photooxydative reaction and form 8hydroxy-2-deoxyguanosine (8-0HdGI as a genotoxic product. Topically extra virgin olive oil (EVOOI can decrease 8-0HdG formation among UVB irradiated-hairless mice epidermal cells. Such effect in human skin has never been discovered.Objective: To know the effect of topically EVOO in UVB induced-8-0HdG formation in human epidermal cells.Method: A simple experiment was performed on cultured human foreskins. The foreskins were divided into 3 groups: group was treated with 100mJ/cm2 UVB + topical EVOO, group B with 100mJ/cm2 UVB, and group C as control. All skin was cultured in completed DMEM and fixation was performed at one and 24 hours. 8-0HdG expression was determined immunohistochemically with antibody anti 8-0HdG and measured based on histogram of selected colour of Adobe photoshop.Results: The mean of 8-0HdG expression in experimental groups: (8.02:t 13.81, (26.95:t 23.231. and 14.96:t 7.141, respectively (p =0.0001 at an hour; (14.91 :t30.63I, (37.58:t 25.631. and (8.76:t 10.941 respectively (p = 0.0001 at 24 hours.Conclusion: Extra virgin olive oil was proved to reduce the 8-0HdG formation in exposed human skin-UVB. and may be developed to be anti-photocarcinogenesis active ingredient topically.Kata kunci:Extra virgin olive oil, UVB, 8-OHdG, human Skin